Analisis Daya Tarik Wisata Air Terjun Ilohu'uwa Kecamatan Bone Kabupaten Bone Bolangoatan Bone Kabupaten Bone Bolango - Daud, Dian Mentari; Eraku, Sunarty Suly; Rusiyah, Rusiyah (-, 2024)
This research aims to analyze the tourist attraction of Ilohu'uwa Waterfall using descriptive qualitative research methods. Data collection in research was carried out using observation, interviews and literature study methods. The research population used was waterfall tourism managers, the community and tourists. The number of samples in this study was 80 respondents. The results of the research show that the Ilohu'uwa Waterfall tourist attraction has good attractiveness by paying attention to the main components of tourism, namely natural tourist attractions, accessibility, and facilities and infrastructure. For natural tourist attractions which are tourist attractions, a score of 86.5% was obtained, categorized as high suitability and has a beautiful panorama. Furthermore, the results of the analysis on accessibility obtained a value of 64,3%, categorized as moderate feasibility with good accessibility but still needs to be improved and paid attention to by the government and government. Then the results of the analysis of facilities and infrastructure obtained were 48,5%, categorized as moderate feasibility and the supporting facilities and infrastructure were adequate but needed to be improved.